Conceptual framework for identifying polymers of concern - Suh, Sangwon; Boulay, Anne-Marie; Fantke, Peter; Li, Dingsheng; Menon, Dilip; Meys, Raoul; Milà i Canals, Llorenç (Frontiers in Sustainability, 2024)
With the increasing global concern over plastics’ environmental and human health impacts, the urgency for effective regulatory measures is evident. The UN Environment Assembly's initiative to establish an international, legally binding instrument via the Intergovernmental Negotiating Committee (INC) on Plastic Pollution marks a significant step towards addressing this issue. However, the vast diversity of plastic types and their myriad applications present a complex challenge in pinpointing the most critical targets for regulation. This study builds on the existing body of literature to outline potential key criteria for identifying Polymers of Concern (PoC). We recommend a dual-focused definition of PoCs considering both (1) the type of the plastics and (2) their domain of applications based on the environmental and human health impacts throughout the polymer’s life cycle. Recognizing the current gaps in our understanding of the full spectrum of plastics’ impacts across their life cycles, we suggest adopting a precautionary approach that factors in the volume of plastics entering natural ecosystems alongside their life cycle impacts as reported in the literature. We then bring forward existing data on the assessment of some of the main polymer types and applications. We propose that policymakers examine a wide spectrum of strategies including not only bans and phaseouts but also economic incentives, innovation, and the redesign of plastic materials and products to mitigate the adverse impacts of PoCs. We further emphasize the importance of thoroughly assessing the feasibility, costs, and environmental, social and economic implications of alternative materials to avoid “regrettable substitution.” We conclude by identifying existing knowledge gaps and emphasizing the need for further research to refine the proposed criteria for identifying PoCs.